Optimizing Marketing Strategies to Boost Purchase Intentions and Behaviors in the Creative Economy - Agustin, Aming Putri; Isa, Muzakar (Jurnal Manajemen Bisnis, 2025)
Research aims: This study aimed to analyze the influence of store image, brand image, and advertising on consumers' purchase intentions and behaviors.Design/Methodology/Approach: Data were collected through an online survey targeting visitors of Ngarsopuro Night Market, using purposive sampling. A total of 200 respondents participated, corresponding with the sample size recommended in previous studies. Moreover, the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) method, processed via SmartPLS version 3.Research findings: The results showed that brand image, store image, and advertising significantly impacted purchase intentions. Even though brand image and advertising influenced purchasing behaviors, store image did not have a significant effect. The result also showed that purchase intentions fully mediated the relationship between brand image, store image, advertising, and purchasing behaviors. Theoretical Contribution/Originality: The Theory of Planned Behavior (TPB) was refined by emphasizing the importance of brand-related attributes over traditional factors like store image, which was found to be insignificant in this context.Practitioners/Policy Implications: The recommendation was to improve the competitiveness of traditional markets in the creative economy by strengthening brand image with local cultural elements, improving store aesthetics, leveraging advertising strategies, and fostering vendor innovation through training and collaborations. Research Limitations/Implications: This study had a limited sample size and used an online survey method. Therefore, it is crucial to expand the geographical scope of the study and combine online surveys with direct interviews to obtain more accurate and detailed information.